Study of regional energy systems using the technocentric approach - Zavyalov N.V.; Paskar I.N.; Lebedev G.M. (Горное оборудование и электромеханика)
The article analyzes the functioning Kuzbass energy system in three projections according to the two studied criteria, processes and describes the results of the study, evaluates electricity consumption by economic sectors of the Russian Federation, describes in detail the mathematical software to implement the study based on the technocentric approach, finds points of the proposed optimization impact, which justify the implementation of distributed generation facilities (including - on the o Ranking analysis in the course of the conducted research includes three stages, which allow to describe complex technological systems as a result: interval estimation, rationing and forecasting. The advantages of the technocentric approach to the power system analysis lie in the study of changing technological systems as a unified whole, which is characterized by stable parameters. The study is based on current statistical data from the System Operator of the Unified Energy System (hereinafter - SO UES), data from the Federal State Statistics Service, as well as officially published relevant documents of the Government of the Russian Federation, schemes and programs of prospective development of the electric power industry (hereinafter - SIPRE) of all subjects of the Russian Federation. Among the pronounced individuals of the technocenosis of the regional power system under study, three sectors of the economy were identified - mining, manufacturing and transport. As a result of the study the deviation value of the optimization parameter (the level of electricity consumption by industries, installed capacity of power plants and their number) was determined, the prospective nature of the behavior of abnormal indicators, separated from the confidence interval was studied. It is noted that the current shortage of electricity in the energy system will grow due to the progressive volumes of production on the territory of the studied subject of the Russian Federation.